Model Akselerasi Pembelajaran Kitab Kuning Melalui Metode Nubdzatul Bayan di pesantren Al-Majidiyah Pamekasan - Sayyi, Ach.; Fithriyah, Imaniyatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Entering the era of society 5.0, the interest of Islamic students in pursuing knowledge of Islamic, social, religious, political, economic, and legal studies derived from the yellow books is very low, considering that there are several books that have been translated and printed in book form, and some even in the form of digital applications that can be easily read by students and the wider community. However, the ability to read, interpret, and understand the contents of the yellow books is one of the requirements for students to be considered as such. The research aims to understand, analyze, and interpret the findings of the implementation of the nubdzatul bayan method and the model of accelerating the reading of the yellow books. The writing method used a qualitative approach with phenomenological type. Data was obtained through observation, interviews, and document studies. The collected data was then described, analyzed, and interpreted based on theoretical and philosophical principles by examining the research data through the interactive analysis of Miles and Huberman, starting from data collection, reduction, presentation, and verification. The results of this research show that 1) the acceleration program in learning the yellow book is an effort to appreciate the achievements of students, an effort to increase the effectiveness and efficiency of the process of mastering the yellow book, an effort to increase spiritual, intellectual and emotional intelligence in a balanced manner, and an effort to provide recognition for the achievements of students . The acceleration program using the nubdzatul bayan method in learning the yellow book at the Al-Majidiyah Islamic boarding school is implemented through 5 stages or fans starting from fan mubtadi', fan Nubdzatul Bayan, fan Faraidl, fan arudl, and fan arudl. Meanwhile, the model for accelerating mastery of the yellow book through the application of the nubdzatul bayan method is illustrated through five components contained in the learning process, namely planning, materials, strategies, tools/media and evaluation..